Telomere length is independently associated with age, oxidative biomarkers, and sport training in skeletal muscle of healthy adult males. (3rd June 2018) - Magi, Fiorenza; Dimauro, Ivan; Margheritini, Fabrizio; Duranti, Guglielmo; Mercatelli, Neri; Fantini, Cristina; Ripani, Francesca Romana; Sabatini, Stefania; Caporossi, Daniela
Abstract: In skeletal muscle, which mainly contains postmitotic myonuclei, it has been suggested that telomere length remains roughly constant throughout adult life, or shortens in response to physiopathological conditions in muscle diseases or in the elderly. However, telomere length results from both the replicative history of a specific tissue and the exposure to environmental, DNA damage-related factors, therefore the predictive biological significance of telomere measures should combine the analysis of the various interactive factors. In the present study, we analysed any relationship between telomere length [mean and minimum terminal restriction fragment (TRF) length] chronological age, oxidative damage (4-HNE, protein carbonyls), catalase activity, and heat shock proteins expression (αB-crystallin, Hsp27, Hsp90) in semitendinous muscle biopsies of 26 healthy adult males between 20 and 50 years of age, also exploring the influence of regular exercise participation. The multiple linear regression analysis identified age, 4-HNE, catalase, and training status as significant independent variables associated with telomere length and jointly accounting for ∼30–36% of interindividual variation in mean and/or minimum TRF length. No association has been identified between telomere length and protein carbonyl, αB-crystallin, Hsp27, and Hsp90, as well as between age and the variables related to stress response. Our results showed that skeletal muscle from healthy adults displays an age-dependent telomere attrition and that oxidised environment plays an age-independent contribution, partially influenced by exercise training.